Evaluation of functional and radiological outcome of core decompression with autologous corticocancellous bone grafting and intralesional zolendronic acid in early stages of avascular necrosis of femoral head - Devdass, Varun; Kumar, Deepak; Shetty, Karan (International Journal of Research in Orthopaedics, 2024)
Background: Avascular necrosis (AVN) of the femoral head is a progressive condition leading to bone necrosis, collapse, and joint dysfunction. Core decompression with autologous corticocancellous bone grafting is a common treatment option for early-stage AVN. This study aimed to compare the functional and radiological outcomes of core decompression with autologous corticocancellous bone grafting alone versus the same procedure with the addition of intralesional zolendronic acid in patients with early-stage AVN. Methods: A randomized controlled trial was conducted with 20 patients (26 hips) diagnosed with early-stage AVN (Ficat stages I and II). Patients were randomly allocated into two groups. Group A underwent core decompression with bone grafting, while group B received the same procedure with the addition of zolendronic acid. Functional outcomes were assessed using the Harris hip score (HHS), pain relief was measured using the visual analog scale (VAS), and radiological progression was evaluated using MRI scans at 3, 6, and 12 months postoperatively. SPSS version 23 was used for data analysis. Results: Group B demonstrated significantly greater improvements in pain relief and functional outcomes at all follow-up intervals (p<0.05). The mean HHS in group B improved from 50.5±8.0 preoperatively to 88.0±5.5 at 12 months, while group A showed an improvement from 49.0±7.7 to 79.2±6.6. Conclusions: The addition of Zolendronic acid to core decompression and autologous corticocancellous bone grafting significantly enhances both functional and radiological outcomes in patients with early-stage AVN.